State of health and roads of his improving at children of school age in special medical groups. - Sidorchenko E. N. (Kharkov National Pedagogical University, 2010)
Tendencies of an aggravation of symptoms of health of children are construed. It is exhibited magnifications of variety and a degree of gravity of diseases. Directions of lowering of the negative tendencies of lowering of a level of health of schoolboys in special medical groups are recommended. It is recommended to grant for schoolboys considerably major requirement for exercises by physical exercises. It is indicated on positive motivations of an estimation controlling function. The accent on necessity to activate a motor performance mades up. A separate direction is conductings provisions on raise of morphofunctional and power possibilities of an organism of schoolboys.